(untitled) (International Journal of Food and Nutritional Sciences, 2022)
- Image processing is a significant field in computer science and artificial intelligence that focuses on the manipulation and analysis of images to enhance their quality or extract valuable information. This paper delves into the fundamentals, methodologies, and applications of image processing. It explores various techniques including filtering, edge detection, segmentation, and morphological operations. Furthermore, the paper discusses the advancements in image processing facilitated by deep learning and the broad range of applications spanning medical imaging, remote sensing, and computer vision. Image processing, a pivotal area within computer science and artificial intelligence, focuses on the manipulation and analysis of images to enhance their quality or extract valuable information. This paper provides an in-depth exploration of the fundamental techniques and methodologies in image processing, including image enhancement, edge detection, segmentation, and morphological operations. It also highlights the advancements brought by deep learning technologies such as convolutional neural networks (CNNs) and generative adversarial networks (GANs). The paper further examines a broad spectrum of applications, from medical imaging and remote sensing to computer vision. Through a comprehensive review, this study underscores the significant impact of image processing on various technological domains and its potential for driving future innovations.